2010
DOI: 10.1007/s11136-010-9771-9
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and related variables in patients with ankylosing spondylitis

Abstract: In patients with AS, the most significant variables associated with QoL were BASDAI, BASFI, fatigue and pain. ASQoL was noted to be a short, rapid and simple patient-reported outcome (PRO) instrument and strongly correlated with SF-36 subscales.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
67
1
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(79 citation statements)
references
References 14 publications
8
67
1
3
Order By: Relevance
“…20,21 Furthermore, in our study the BASFI results had no correlation with age. This is in line with Turkish and Finnish studies.…”
Section: Discussioncontrasting
confidence: 76%
“…20,21 Furthermore, in our study the BASFI results had no correlation with age. This is in line with Turkish and Finnish studies.…”
Section: Discussioncontrasting
confidence: 76%
“…[28][29][30][31][32][33][34] Bodur et al studied the quality of life and related variables in ninehundred and sixty-two patients with AS. 13 In conclusion, they have found in patients with AS that, the most significant variables associated with quality of life were BASDAI, BASFI, fatigue and pain. Analay et al investigated the effectiveness of intensive group exercise in 45 AS patients and found that group exercise in hospital could have been more effective than home-based exercises at reducing impairment associated with ankylosing spondylitis.…”
Section: Discussionmentioning
confidence: 83%
“…These results were found to be consistent with previous studies. 4,[6][7][8][9][10][11][12][13]25 A positive relation was found between duration of the disease and BASMI in patients with AS. As the duration of disease increased, the extent of its effect on the patient increased and it affected the patient's mobility negatively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But the major challenge is the widely observed fact that most AS patients do not exercise on a regular basis. Various researchers have reported that as many as 82%, 77% and 65.6% of AS patients do not do any regularly exercising [34][35][36][37]. The main challenge to the success of exercise programs is declining motivation, which leads to a loss of compliance [4,34].…”
Section: Discussionmentioning
confidence: 99%